Lost bodies : prostitution and masculinity in Chinese fiction - Zamperini, Paola (Women and gender in China studies ;, 2010)
This important contribution to the study of early modern Chinese fiction and representation of gender relations focuses on literary representations of the prostitute produced in the Ming and Qing periods. Following her heavily symbolic body, the present work maps this fictional heroine's journey from innocence to sex-work and beyond. This crucial angle allows the author to paint a picture of gender identity, sexuality, and desire that is at once unitary and multi-layered, and that comes to illuminate some of the major themes in the construction of Chinese modernity.